Soil development and mineral transformations along a one‐million‐year chronosequence on the Galápagos Islands. Issue 6 (21st October 2021) - Candra, I Nyoman; Gerzabek, Martin H.; Ottner, Franz; Wriessnig, Karin; Tintner, Johannes; Schmidt, Greta; Rechberger, Maria V.; Rampazzo, Nicola; Zehetner, Franz
Abstract: The Galápagos archipelago is a well‐suited model ecosystem for investigating soil evolution. Here, we study mineral transformations and pedogenesis of the volcanic soils of Galápagos in response to weathering duration (1, 500–1, 070, 000 yr) and climate (humid vs. dry). Our results show that soil pH, electrical conductivity, organic C content, cation exchange capacity (CEC), and water retention decreased whereas clay content and bulk density increased with soil age under humid climate. Andic properties were expressed in soils ≤4, 300 yr old, but disappeared relatively early in pedogenesis and were absent in soils ≥26, 000 yr old. The clay fraction of the young andic soils (≤4, 300 yr old) was dominated by allophane and ferrihydrite. After 26, 000 yr of pedogenesis, illitic–vermiculitic phases were predominant, and in the older soils (≥166, 000 yr old), kaolinite, hematite, and gibbsite prevailed. The sequence of soil orders from the youngest to the second oldest site was Histosol–Andisol–Alfisol (vermiculitic)–Alfisol (parasesquic)–Ultisol. The oldest soil of the humid chronosequence (1, 070, 000 yr old) met all diagnostic criteria for an Oxisol except for the required low CEC. The soils at two dry comparison sites were less developed with low clay contents and vitric materials at 26, 000 yr of age (Entisol), and dominantly smectitic clay mineralogy and pronounced shrink–swell features at 813, 000 yr of age (Vertisol). Our results highlight a rapid transition through the Andisol stage during early pedogenesis as well as strongly divergent pedogenic development in humid vs. dry zones of the Galápagos Islands, both of which have important bearings on soil functioning and ecosystem evolution on this unique archipelago. Core Ideas: Mineral transformations were allophane → vermiculite–illite → kaolinite, hematite, gibbsite. The sequence of soil orders was Histosol → Andisol → Alfisol → Ultisol. Rapid transition through the andic stage occurred during early pedogenesis. The volcanic origin and andic past were still reflected in the oldest soils (Andic subgroups). Soils at drier sites were less developed (young, Entisol; old, Vertisol).